A model for organisational readiness in information technology (IT) project implementation in the Malaysian construction industry / Nur Mardhiyah Aziz - Nur Mardhiyah, Aziz (2013)

(untitled)
In a highly competitive environment, it is imperative for the construction industry (CI) to adopt IT/IS to stay ahead. Despite the numerous benefits of IT/IS adoption, findings show poor success rate of IT/IS implementation in the CI. Researchers has identified the failure is related to the people issues within an organisation. People issues are clearly significant, yet neglected, and need to be considered for successful IT/IS implementation. Thus, to measure people readiness or capabilities of an organisation prior to new implementation of IT/IS is extremely important to ensure its successful implementation. This study begins with reviewing several e-readiness models that have been developed to measure readiness or capabilities by various groups and institutions. Several limitations have revealed that such models were restricted to assess the current capabilities without indicating previous achievements and recommendations for improvement. Furthermore, majority of the available readiness models for IT/IS implementation does not focus directly on the people issues specifically for the CI. Therefore, this research attempt to address these limitations by focusing on the people readiness issues in the CI. A People e-Readiness Maturity Model (PeRMM) was developed to assist the construction organisation to successfully implement IT/IS by identifying their readiness level prior to IT/IS investments. Prior to developing the PeRMM, people critical success factors (CSFs) were identified through the literatures dated from year 2000 to 2013, which reveal 21 people CSFs. Seven IT managers were selected to participate in the pilot study to confirm the existence of the 21 CSFs obtained. Findings from the pilot study revealed two additional people CSFs; personal management competencies and independent. The 23 people CSFs were then used to design the questionnaire survey. The questionnaire was sent to 1000 Malaysian construction organisations ranging from small to large-sized, and received 31.1% iv responses. Several analysis were performed in shortlisting the people CSFS to be included in the preliminary people e-readiness maturity model. Subsequently, 5 construction organisations participated in the validation exercise to validate the model with current practices. This model is anticipated to assess the organisation’s previous achievements, current readiness level and help them to determine their future target as well as identify their readiness gaps that need to be filled. This model will also act as a measurement tool that can help construction organisations to identify the improvements needed to successfully implement IT/IS. It is expected that this model will contribute to the IT/IS field by adding to new dimensions of IT/IS evaluation which focus on the people perspective.